PENEGAKAN HUKUM TERHADAP ROKOK ILEGAL OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA CUKAI KUDUS - Syaharani, Pramitha Putri; Hernanda, Trias; Novitasari, Arina (Jurnal Ilmiah Dinamika Hukum, 2026)
The circulation of illegal cigarettes in Kudus Regency remains a serious problem that is detrimental to the state and disrupts a healthy business competition climate. This study aims to analyze the forms and mechanisms of law enforcement by the Kudus Customs and Excise Supervision and Service Office against these violations based on Law Number 39 of 2007 concerning Excise, and to identify inhibiting factors in its implementation. The research method used is an empirical juridical approach with a qualitative descriptive research type through interviews with officials of the Kudus Customs and Excise Supervision and Service Office and a literature study of related documents and regulations. The circulation of illegal cigarettes is still found in various forms of violations, with plain cigarettes without excise stamps being the most frequently found type. The resulting impacts include reduced state revenue, disrupted competitiveness of the legal cigarette industry, and low levels of public legal compliance. In its implementation, the Kudus Customs and Excise Supervision and Service Office faces obstacles in the form of limited personnel and facilities, difficulties in location searches, and low public legal awareness. This research is expected to contribute to increasing the effectiveness of law enforcement in the excise sector and support efforts to eradicate the circulation of illegal cigarettes in Indonesia